Menstrual Hygiene Practices and Associated Factors among Post-Menarche Primary-School Girls in Semi-Rural Indonesia: A Mixed-Methods Study - Risna Dewi Yanti; Sabarinah Prasetyo; Agustin Kusumayati; Erna Herawati; Loveria Sekarini (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Menstrual hygiene management (MHM) remains a significant public health issue, particularly among primary school girls in low- and middle-income countries. Poor menstrual hygiene is associated with an increased risk of reproductive tract infections and may increase vulnerability to sexually transmitted infections (STIs). In Indonesia, inadequate practices remain common, including in semi-rural areas such as Garut Regency, where limited sanitation and family dynamics influence menstrual health behaviors. Methods: This study used a sequential explanatory mixed-methods design. A total of 83 primary school girls who had experienced menarche were included in the quantitative phase and analyzed using multivariate logistic regression. 21 informants were purposively selected for in-depth interviews based on school variation, knowledge level, maternal support level, and menstrual hygiene practice category. All selected informants completed the interviews, and all completed interviews were included in the thematic analysis Results: High knowledge was strongly associated with good MHM practices (OR = 13.60; 95% CI: 3.38–54.71; p < 0.001 ). After adjusting for maternal support and sanitary pad availability, girls with adequate knowledge had 13.6 times higher odds of good menstrual hygiene practices . Qualitative findings suggested that maternal support may facilitate the application of menstrual hygiene knowledge through emotional guidance, practical assistance, and the normalization of menstruation. Conclusion: High knowledge was the only statistically significant factor associated with good MHM practices in the adjusted quantitative model. Maternal support, although not statistically significant in the multivariable analysis, emerged in the qualitative findings as a contextual facilitator that may support the application of menstrual hygiene knowledge in daily practice.